Efficiency gains from team-based coordination ; large-scale experimental evidence - Francesco Feri; Bernd Irlenbusch; Matthias Sutter (Max Planck Institute for Research on Collective Goods, 2009)
The need for efficient coordination is ubiquitous in organizations and industries. The literature on the determinants of efficient coordination has focused on individual decision making so far. In reality, however, teams often have to coordinate with other teams. We present a series of coordination experiments with a total of 1,101 participants. We find that teams of three subjects each coordinate much more efficiently than individuals. This finding adds one important cornerstone to the recent literature on the conditions for successful coordination. We explain the differences between individuals and teams using the experience weighted attraction learning model.
Keywords: C71; C91; C92; 330; Gruppenentscheidung; Kooperatives Spiel; Lernprozess; Wirtschaftliche Effizienz; Test